Autoestima en estudiantes de carreras técnicas y universitarias - Aguilar Florez, Juana Silvana (2024)
The purpose of this study was to determine whether university students have better self-esteem than students from technological institutes in Arequipa. The participants were 770 students, 385 from 4 technological institutes (2 public and 2 private) y 385 students from 2 universities (1 public and 1 private), 608 (79%) were men and 162 (21%) females. A demographic form and the Culture Independent Self-Esteem Inventory (CFSEI-2) (Battle, 1992) were administered. It was found that high school students have significantly better self-esteem than college students, that females have better self-esteem than males, that self-esteem is better at ages 16 to 19 years, and that college electronics students and technology mechanics students have better levels of self-esteem.